ANALISA KAPASITAS PENYEBERANGAN SEBIDANG DI JALAN ASIA AFRIKA SENAYAN JAKARTA - M Subhan Alamsyah; Winoto Hadi; Daryati Daryati (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2020)
The purpose of this study is to provide an evaluation on pedestrian crossing facility on Asia Afrika street, Senayan Jakarta based on requirement on Directorate General of Transportation and also provided a new suggestion for an alternative pedestrian crossing facility on Asia Afrika street especially in front of Senayan City. The alternative of pedestrian facility obtained by observation on site of the location by observing the traffic of pedestrian whose crossed the street of Asia Afrika and the traffic of all vehicle that crossed the street at peak hours. The observation also included a geometric condition of the street and pedestrian facility on site. As additional study, a survey on 100 pedestrians also being held to determine the characteristic of pedestrian. The result of this study found that the available pedestrian crossing facility on site which is a zebra cross is not capable of providing comfort and safety to pedestrian. Because based of all calculation requirement on MKJI 2007 the Asia Afrika street should provide a pedestrian crossing bridge or a pedestrian crossing tunnel for pedestrian crossing facility which is safer and more comfortable.